Electrode membrane, preparation method thereof and battery
By introducing alkali metal-containing composite oxides into the electrode film as protective components to form a surface protective layer, the problem of mismatch between the interface between the sulfide solid electrolyte and the active material is solved, and the electrochemical performance of the battery is improved.
Patent Information
- Application Number
- CN202411395135.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-11
AI Technical Summary
There is structural mismatch and poor interface stability between the sulfide solid electrolyte and the active material, resulting in interface side reactions and elemental interdiffusion, affecting the cycling performance of the battery.
An electrode film is used, which includes an active substance, a sulfide solid electrolyte, a conductive agent, a binder and a protective component, which includes an alkali metal-containing composite oxide to form a surface protective layer to improve interface compatibility.
By constructing a surface protective layer, the interface problems between the sulfide solid electrolyte and the active material are effectively alleviated, and the transmission rate of lithium ions and the electrochemical performance of the battery are improved.
Smart Images

Figure CN119419271A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrode film and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, large-scale energy storage and other fields, and have become an indispensable part of daily life. However, currently commercial lithium-ion batteries generally use organic liquid electrolytes, whose flammability, corrosion, leakage, expansion and other characteristics bring great safety hazards to the battery system. Unlike organic liquid electrolytes, inorganic solid electrolytes are not easy to burn, allowing the matching of high specific energy positive electrodes and metal lithium negative electrodes. Therefore, replacing liquid electrolytes with inorganic solid electrolytes can further improve the energy density and safety of batteries, reduce flammability, and increase battery cycle life. At present, the more mature inorganic solid electrolytes are mainly sulfide and oxide solid electrolytes. Compared with oxide electrolytes, sulfide electrolytes have high ionic conductivity and good ductility, showing good application prospects.
[0003] However, there are still more or less problems in the practical application of sulfide solid electrolytes, such as structural mismatch and poor interface stability between sulfide solid electrolytes and active materials. During the electrochemical cycle, serious interface side reactions and element interdiffusion will occur between the electrolyte and the active material, resulting in a sharp increase in interface impedance, loss of active lithium ions and rapid decay of battery capacity. These problems limit the performance of sulfide all-solid-state batteries.
[0004] In the related art, in order to solve the interface problem between the sulfide solid electrolyte and the active material, the interface between the sulfide solid electrolyte and the active material is usually modified to eliminate the space charge layer, inhibit the interface side reaction, and stabilize the interface structure. At present, in order to alleviate the interface problem, the modification methods mainly include surface coating, core-shell structure design, ionic liquid injection, composite electrolyte construction, particle morphology and size design, etc. However, these methods often have the disadvantages of slow lithium ion transmission rate, mismatch between the modified layer and the main material structure, complex process or high preparation cost.
[0005] In view of this, it is necessary to research and develop more effective technical solutions to solve the interface problem between sulfide solid electrolytes and active materials, and this application is specially proposed. Summary of the invention
[0006] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides an electrode film and a preparation method thereof and a battery, which can alleviate the problems of structural mismatch and poor interface stability between the current sulfide solid electrolyte and the active material, and serious side reactions between the two during the electrochemical cycle, and is conducive to improving the comprehensive electrochemical performance of the battery.
[0007] In order to solve the above technical problems, this application is implemented as follows:
[0008] According to one aspect of the present application, an embodiment of the present application provides an electrode membrane, the electrode membrane comprising: an active material, a sulfide solid electrolyte, a conductive agent, a binder and a protective component;
[0009] Wherein, at least part of the protective component is located on the surface of the active material to form a surface protective layer, and / or, at least part of the protective component is located on the surface of the sulfide solid electrolyte to form a surface protective layer;
[0010] The protective component includes a composite oxide containing an alkali metal.
[0011] In addition, the electrode film according to the present application may also have the following additional technical features:
[0012] In some of the embodiments, the active material, the sulfide solid electrolyte and at least one layer of the surface protective layer form a core-shell structure, the core of the core-shell structure is the active material, the shell of the core-shell structure includes the sulfide solid electrolyte and at least one layer of the surface protective layer, and along the direction away from the core, the surface protective layer, the sulfide solid electrolyte, and the surface protective layer are arranged in sequence; the surface protective layer is formed by the protective component.
[0013] In some embodiments, the mass of the protective component is A, the sum of the masses of the active material and the sulfide solid electrolyte is B, and A and B satisfy: A is 0.1% to 10% of B.
[0014] In some embodiments, the thickness of the surface protection layer is ≤200 nm.
[0015] In some embodiments, the electrode film is a positive electrode film, and the chemical formula of the protective component is LiM a OX b , wherein M includes one or more of Ta, Nb, Zr, Al, Fe or Y, X includes one or more of Cl, Br or F, 0≤a≤1, 2≤b≤4.
[0016] In some embodiments, the positive electrode film satisfies at least one of the following characteristics (1) to (7): (1) the X-ray diffraction spectrum of the protective component has diffraction peaks at positions where the diffraction angle 2θ value is 14°±0.5°, 24.5°±0.5°, and 31°±0.5°, respectively; (2) the active material is a positive electrode active material, and the positive electrode active material includes LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 3 、LiNi x Co y Mn z O 2 (x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1), LiNi x Co y Al z O 2 (x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1), xLi 2 MnO 3 (1-x)LiTMO 2 (TM = at least one of Ni, Mn, Co or Al, 0<x<1), LiMn 2 O 4 , Li 4 Ti 5 O 12 、Li(Ni 0.5 Mn 1.5 ) 4 、LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 or LiMn x Fe 1-x PO 4 (0<x<1) or more; (3) the sulfide solid electrolyte includes Li x MP y S z (M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12), Li 7-x-y PS 6-x-y Cl x X y (X is a halogen element, 0≤x≤1.7, 0≤y≤1.7), xLi 2 S·(100-x)P 2 S 5(70≤x≤80) or yLiI·zLiBr·(100-yz)(xLi 2 S·(100-x)P 2 S 5 )(70≤x≤80, 0≤y≤30, 0≤z≤30); (4) the particle size of the active material is 20nm~50μm; (5) the particle size of the sulfide solid electrolyte is 10nm~20μm; (6) the mass ratio of the sulfide solid electrolyte to the active material is 1:9~4:6; (7) in the electrode film, the mass content of the conductive agent is 0.05%~5%, and the mass content of the binder is 0.05%~5%.
[0017] In some embodiments, the electrode film is a negative electrode film, and the chemical formula of the protective component is Li v P w N x S y O z , wherein N includes one or more of Sn, Sb, B, Bi, Fe or Zn, 7≤v≤10, 2≤w≤4, 0≤x≤1, 5≤y≤8, 0≤z≤5.
[0018] In some embodiments, the negative electrode film satisfies at least one of the following characteristics (1) to (7): (1) in the X-ray diffraction spectrum of the protective component, there are diffraction peaks at the positions of diffraction angles 2θ of 27°±0.5°, 30°±0.5°, 32.5°±0.5°, 40.5°±0.5°, and 50°±0.5°, respectively; (2) the active material is a negative electrode active material, and the negative electrode active material includes one or more of lithium titanate, metal Li, In, Sn, and their respective alloys, carbon-based materials, or silicon-based materials; (3) the sulfide solid electrolyte includes Li x MP y S z (M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12), Li 7-x-y PS 6-x-y Cl x X y (X is a halogen element, 0≤x≤1.7, 0≤y≤1.7), xLi 2 S·(100-x)P 2 S 5 (70≤x≤80) or yLiI·zLiBr·(100-yz)(xLi 2 S·(100-x)P 2 S 5)(70≤x≤80, 0≤y≤30, 0≤z≤30); (4) the particle size of the active material is 20nm~40μm; (5) the particle size of the sulfide solid electrolyte is 10nm~20μm; (6) the mass ratio of the sulfide solid electrolyte to the active material is 1:9~4:6; (7) in the electrode film, the mass content of the conductive agent is 0.05%~5%, and the mass content of the binder is 0.05%~5%.
[0019] According to another aspect of the present application, an embodiment of the present application provides a method for preparing an electrode film as described above, the method comprising the following steps:
[0020] mixing an active material, a sulfide solid electrolyte, and a protective component precursor to obtain a mixture;
[0021] sintering the mixture to form a surface protection layer on the surface of the active material and / or the sulfide solid electrolyte to obtain a composite material;
[0022] The composite material is mixed with a conductive agent and a binder, and the electrode film is prepared through a film-forming process.
[0023] In some embodiments, the preparation method satisfies at least one of the following features (1) to (6): (1) the electrode film is a positive electrode film, the protective component precursor includes a lithium source and a halogen compound, wherein the lithium source includes LiOH, Li 2 CO 3 or Li 2 O, the halogen compound includes NbCl 5 、TaCl 5 、ZrCl 4 、AlCl 3 、FeCl 3 , YCl 3 ,NbF 5 or TaF 5 (2) the electrode film is a negative electrode film, the protective component precursor includes a lithium source, a phosphorus source and an oxide or a sulfide, wherein the lithium source includes LiOH, Li 2 CO 3 , Li 2 O or Li 2 S, the phosphorus source includes P 2 S 5 or P 2 O 5 One or more of the oxides or sulfides, wherein the oxides or sulfides include SnS 2 , Sb 2 S3 , B 2 O 3 、Bi 2 O 3 SnO 2 、ZnO 2 , Fe 2 O 3 One or more of the following: (3) in the step of obtaining the mixture, the mixing is carried out by ball milling, the ball milling is carried out in an inert atmosphere, the rotation speed of the ball mill is 200 rpm to 800 rpm, and the ball milling time is 1 h to 20 h; (4) in the step of obtaining the composite material, the sintering is low-temperature sintering, the temperature of the low-temperature sintering is 90°C to 350°C, and the low-temperature sintering time is 1 h to 12 h; (5) the film forming process includes a wet film forming process or a dry film forming process; (6) the preparation process of the electrode film is carried out in an environment with a dew point of less than -50°C.
[0024] According to another aspect of the present application, an embodiment of the present application provides a battery, the battery comprising a positive electrode current collector, a positive electrode film, a solid electrolyte layer, a negative electrode film and a negative electrode current collector stacked in sequence;
[0025] Wherein, the positive electrode film comprises the electrode film as described above or the electrolytic film prepared according to the above method; and / or, the negative electrode film comprises the electrode film as described above or the electrolytic film prepared according to the above method.
[0026] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0027] In the embodiment of the present application, the provided electrode film includes an active material, a sulfide solid electrolyte, a conductive agent, a binder and a protective component; and the protective component can form a surface protective layer on the surface of the active material and / or the sulfide solid electrolyte. Thus, by constructing a surface protective layer, the active material and the sulfide solid electrolyte have good compatibility, and the surface protective layer is not easy to fail during the electrochemical cycle, thereby effectively alleviating the interface problem between the sulfide solid electrolyte and the active material in the prior art.
[0028] The electrode membrane of the present application introduces a protective component, which includes a composite oxide containing an alkali metal. No substance with low ionic conductivity is introduced during the modification process, so the surface protective layer has high ionic conductivity and basically does not affect the transmission of lithium ions between the active material and the sulfide solid electrolyte. In addition, the electrolyte uses a high ionic conductivity sulfide solid electrolyte, and lithium ions can be quickly transmitted between the positive electrode layer and the negative electrode layer, which improves the transmission effect of lithium ions and ultimately helps to improve the electrochemical performance of the battery prepared using the electrode membrane.
[0029] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 FIG. 1 is a schematic diagram of the structure of a first battery provided in Example 1 of the present invention;
[0031] Figure 2 FIG. 2 is a schematic diagram of the structure of a second battery provided in Example 2 of the present invention;
[0032] Figure 3 Shown is a schematic structural diagram of a third battery provided in Example 3 of the present invention.
[0033] Description of reference numerals:
[0034] 1- negative electrode current collector;
[0035] 2- negative electrode membrane;
[0036] 3- solid electrolyte layer;
[0037] 4- cathode film;
[0038] 5- positive electrode current collector;
[0039] 6-sulfide solid electrolyte (sulfide solid electrolyte in the positive electrode film);
[0040] 7- positive electrode active material;
[0041] 8- surface protection layer (surface protection layer in the positive electrode film);
[0042] 9-sulfide solid electrolyte (sulfide solid electrolyte in the negative electrode membrane);
[0043] 10- negative electrode active material;
[0044] 11- surface protection layer (surface protection layer in the negative electrode film);
[0045] 12-Battery (solid-state battery). DETAILED DESCRIPTION
[0046] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0047] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0048] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0049] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0050] Among solid electrolytes, sulfide solid electrolytes have the characteristics of high ionic conductivity and good ductility. However, there are structural mismatches or poor interface stability between sulfide solid electrolytes and active materials (active substances), which affects the cycle performance of the battery. Although the interface problems between sulfide solid electrolytes and active materials can be alleviated to a certain extent by modification through surface coating, ionic liquid injection and other means in the prior art, these existing methods often lead to slow lithium ion transmission rate and mismatch between the modified layer and the main material structure, which needs to be further improved.
[0051] Based on the above research, the inventors of this application fully consider the characteristics of sulfide electrolyte materials or the interface problems between sulfide electrolytes and active materials, and adopt specific modification methods to alleviate the structural mismatch and poor interface stability between sulfide solid electrolytes and active materials, and the serious side reactions between the two during the electrochemical cycle; it can also alleviate the problem of slow lithium ion transmission in the positive electrode layer and the negative electrode layer; it can also alleviate the shortcomings of the existing interface modification technology, which is complex, costly, and easy to fail in the interface layer. In view of this, this application provides an electrode film, a method for preparing an electrode film, and a battery, and the application is described in detail below.
[0052] [Electrode film]
[0053] In some embodiments, an electrode film is provided, the electrode film comprising: an active material, a sulfide solid electrolyte, a conductive agent, a binder, and a protective component. That is, in the present application, the electrode film not only comprises an active material, a conductive agent, a binder, and a sulfide solid electrolyte, but also comprises a protective component that can be used to improve the interface problem between the active material and the sulfide solid electrolyte.
[0054] Among them, at least part of the protective component is located on the surface of the active material to form a surface protective layer, and / or, at least part of the protective component is located on the surface of the sulfide solid electrolyte to form a surface protective layer; the protective component includes a composite oxide containing an alkali metal.
[0055] The surface protective layer may be formed of a protective component, for example, a surface protective layer formed of a protective component may be formed on the surface of the active material, and / or a surface protective layer formed of a protective component may be formed on the surface of the sulfide solid electrolyte.
[0056] The protective component may include a complex containing an alkali metal, such as a complex oxide containing an alkali metal, or a complex phosphide containing an alkali metal.
[0057] In the present application, the electrode film can be applied to an electrode sheet, and the electrode sheet can be a positive electrode sheet or a negative electrode sheet, that is, the polarity of the electrode sheet can be a positive electrode or a negative electrode. Thus, the electrode film can be a positive electrode film, or it can also be a negative electrode film. When the electrode film is a positive electrode film, the active material in the electrode film is a positive electrode active material; when the electrode film is a negative electrode film, the active material in the negative electrode film is a negative electrode active material; and based on the different types or properties of the positive electrode active material and the negative electrode active material, the specific composition of the protective component in the positive electrode film and the protective component in the negative electrode film is also different.
[0058] Illustratively, in some embodiments, a precursor of a type of protective component reacts with the sulfide solid electrolyte and the positive electrode active material to form a surface protective layer on the surface of the positive electrode active material and the sulfide solid electrolyte.
[0059] In other embodiments, a precursor of another type of protective component reacts with the sulfide solid electrolyte and the negative electrode active material to form a surface protective layer on the surface of the negative electrode active material and the sulfide solid electrolyte.
[0060] Therefore, the present invention can alleviate the interface problem between the positive electrode active material and the sulfide solid electrolyte in the positive electrode sheet, and can also alleviate the interface problem between the negative electrode active material and the sulfide solid electrolyte in the negative electrode sheet, which is beneficial to improving the electrochemical performance of the battery.
[0061] What is particularly noteworthy is that the present application adopts a protective component as a surface protective layer, which can realize the rapid transmission of lithium ions on the surface of the material and avoid the interfacial reaction between the active substance and the sulfide solid electrolyte; moreover, the sulfide solid electrolyte added to the positive electrode membrane or the negative electrode membrane has high ion conductivity, which can realize the effect of rapid transmission of lithium ions in the positive electrode membrane and the negative electrode membrane.
[0062] According to the electrode membrane provided by the present invention, by constructing a surface protection layer, it has good compatibility with the active material and the sulfide solid electrolyte, can avoid the interface reaction between the active material and the sulfide solid electrolyte, and the surface protection layer is not easy to fail during the electrochemical cycle, so that the interface problem between the sulfide solid electrolyte and the active material in the prior art can be effectively alleviated. In addition, the protective component introduced in the electrode membrane of the present application includes a composite oxide containing an alkali metal, and no substance with low ionic conductivity is introduced during the modification process, so the surface protection layer has a high ionic conductivity, which basically does not affect the transmission of lithium ions between the active material and the sulfide solid electrolyte. In addition, the electrolyte adopts a sulfide solid electrolyte with high ionic conductivity, and lithium ions can be quickly transmitted in the positive electrode membrane and the negative electrode membrane, which improves the transmission effect of lithium ions and ultimately helps to improve the electrochemical performance of the battery using the electrode membrane.
[0063] In addition, the preparation process of the electrode membrane is simple in process flow, convenient in operation, easy to implement, and conducive to industrial application.
[0064] It should be noted that the electrode film of the present application can be applied to a lithium battery, and when the electrode film is applied to a lithium battery, the alkali metal in the above-mentioned protective component can be lithium. Although in the specific embodiments, the present application is explained using a lithium battery as an example of a battery, the battery of the present application is not limited to a lithium battery. For example, in other embodiments, when the electrode film is applied to a sodium battery, a magnesium battery, or other battery, the same or similar principles are used.
[0065] In some embodiments, the active material, the sulfide solid electrolyte and at least one surface protective layer form a core-shell structure, the core of the core-shell structure is the active material, the shell of the core-shell structure includes a sulfide solid electrolyte and at least one surface protective layer, and along the direction away from the core, the surface protective layer, the sulfide solid electrolyte, and the surface protective layer are arranged in sequence; the surface protective layer is formed by a protective component.
[0066] In the electrode membrane of the present application, the active material, the sulfide solid electrolyte and the surface protective layer can form a core-shell structure, and it is a multi-layered core-shell structure, which includes, from the inside to the outside: an inner core, a surface protective layer, a sulfide solid electrolyte and a surface protective layer; wherein the inner core is the active material, and the outer shell or shell layer includes the surface protective layer, the sulfide solid electrolyte and the surface protective layer, that is, the outer shell or shell layer includes two layers of surface protective layers and a sulfide solid electrolyte, wherein one layer of the surface protective layer is located between the inner core of the active material and the sulfide solid electrolyte, and the other layer of the surface protective layer is located on the outer surface of the sulfide solid electrolyte.
[0067] In the present application, a surface protection layer is formed or coated on at least part of the surface of the active material, which can be used to avoid the interfacial reaction between the active material and the sulfide solid electrolyte, and alleviate the interfacial problems between the active material and the sulfide solid electrolyte. The surface protection layer is formed or coated on at least part of the surface of the active material, which means that the surface protection layer can completely encapsulate the active material in the surface protection layer, or the surface protection layer can only coat a part of the outer surface of the active material; that is, the surface protection layer can completely coat the active material, or it can coat a part of the surface of the active material. Similarly, a surface protection layer is formed or coated on at least part of the surface of the sulfide solid electrolyte, which can be used to avoid the interfacial reaction between the active material and the sulfide solid electrolyte, and alleviate the interfacial problems between the active material and the sulfide solid electrolyte. The surface protective layer is formed or coated on at least a portion of the surface of the sulfide solid electrolyte, which means that the surface protective layer can completely encapsulate the sulfide solid electrolyte in the surface protective layer, or the surface protective layer can only coat a portion of the outer surface of the sulfide solid electrolyte; that is, the surface protective layer can completely coat the sulfide solid electrolyte, or can coat a portion of the surface of the sulfide solid electrolyte.
[0068] In the preparation process of the electrode membrane of the present application, the raw materials for preparing the protective component can be mixed by mechanical ball milling to obtain a precursor of the protective component. The precursor of the protective component is mixed and contacted with the sulfide solid electrolyte and the active material. Through simple low-temperature sintering, the precursor of the protective component generates dense protective components on the surface of the sulfide solid electrolyte and the active material, respectively, that is, a surface protective layer is formed. Thus, while ensuring that the material surface has high ion conductivity, the effect of inhibiting the mutual diffusion of elements and surface side reactions between the active material and the sulfide solid electrolyte is achieved.
[0069] On this basis, the use of high ion conductivity sulfide solid electrolytes in the positive electrode membrane and the negative electrode membrane can achieve rapid conduction of lithium ions in the positive electrode membrane and the negative electrode membrane, ultimately improving the electrochemical performance of the battery.
[0070] In some embodiments, when the electrode film is used in the positive electrode, the electrode film is a positive electrode film, and the chemical formula of the protective component is LiMa OX b , wherein M can be a metal element, preferably M is selected from transition metal elements, such as, M includes but is not limited to one or more of Ta, Nb, Zr, Al, Fe or Y; X can be a halogen element, such as X includes but is not limited to one or more of Cl, Br or F, 0≤a≤1, 2≤b≤4.
[0071] Preferably, 0<a≤1, 2≤b≤3.
[0072] Preferably, X is selected from Cl or F; more preferably, X is selected from Cl.
[0073] In the present application, in the positive electrode film, the protective component may be referred to as a first protective component.
[0074] As some improvements to the positive electrode film, the protective component (first protective component) has diffraction peaks at diffraction angles 2θ of 14°±0.5°, 24.5°±0.5°, and 31°±0.5°, respectively, in its X-ray diffraction spectrum.
[0075] In the present application, the protective component (first protective component) has diffraction peaks at diffraction angles 2θ of 14°±0.5°, 24.5°±0.5° and 31°±0.5° in an X-ray diffraction spectrum measured by an X-ray diffraction apparatus (XRD) using CuKα1.
[0076] X-ray diffraction analysis spectrum is well known in the art and can be tested by methods known in the art. For example, the X-ray diffraction analysis spectrum of compound A can be measured using CuKα1 radiation with reference to JIS K 0131-1996 General Rules for X-ray Diffraction Analysis.
[0077] As some improvements to the positive electrode film, the active material is a positive electrode active material, and the positive electrode active material can be a positive electrode active material for batteries known in the art. The present application has no particular restrictions on the type of positive electrode active material, as long as the purpose of the present application can be achieved. As an example, the positive electrode active material includes, but is not limited to, LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 3 、LiNi x Co y Mn z O 2 (x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1), LiNi x Co y Al z O 2(x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1), xLi 2 MnO 3 (1-x)LiTMO 2 (TM = at least one of Ni, Mn, Co or Al, 0<x<1), LiMn 2 O 4 , Li 4 Ti 5 O 12 、Li(Ni 0.5 Mn 1.5 ) 4 、LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 or LiMn x Fe 1- x PO 4 One or more of (0<x<1).
[0078] As an example, the positive electrode active material may be selected from LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 3 Any one or a combination of at least two of the above. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0079] Alternatively, the positive electrode active material can be selected from the ternary materials NCM, LiNi x Co y Mn z O 2 , where x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1.
[0080] Alternatively, the positive electrode active material can be selected from the ternary materials NCA, LiNi x Co y Al z O 2 , where x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1.
[0081] Alternatively, the positive electrode active material may be selected from xLi 2 MnO 3 (1-x)LiTMO 2 , wherein TM is selected from at least one of Ni, Mn, Co and Al, and 0<x<1.
[0082] Alternatively, the positive electrode active material may be selected from LiMn2 O 4 , Li 4 Ti 5 O 12 、Li(Ni 0.5 Mn 1.5 ) 4 、LiFePO 4 、LiMnPO 4 、LiNiPO 4 、LiCoPO 4 or LiMn x Fe 1-x PO 4 Any one or a combination of at least two of (0<x<1). For the sake of brevity, the combinations within the above range are not listed one by one.
[0083] However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more.
[0084] In the present application, the positive electrode active material can be a bare positive electrode active material or a surface-modified positive electrode active material, wherein the bare positive electrode active material refers to a positive electrode active material whose surface has not been modified, and the surface-modified positive electrode active material includes but is not limited to a positive electrode active material modified with a metal oxide or a lithium-containing metal oxide.
[0085] As some improvements to the positive electrode film, the particle size of the active material, that is, the positive electrode active material, is 20nm to 50μm; as an example, the particle size of the positive electrode active material can be any point value of 20nm, 30nm, 50nm, 80nm, 100nm, 500nm, 800nm, 1μm, 10μm, 20μm, 30μm, 40μm, 50μm, or any range value between two of them. By making the particle size of the positive electrode active material in the above appropriate range, the processing performance of the material can be improved, and the capacity advantage can also be brought into play, so that the comprehensive electrical performance of the positive electrode film is better. If the particle size is too small, it will affect the energy density, and if the particle size is too large, it will reduce the capacity.
[0086] In some embodiments, when the electrode film is used in the negative electrode, the electrode film is a negative electrode film, and the chemical formula of the protective component is Li v P w N x S y O z , wherein N includes but is not limited to one or more of Sn, Sb, B, Bi, Fe or Zn, 7≤v≤10, 2≤w≤4, 0≤x≤1, 5≤y≤8, 0≤z≤5.
[0087] In the present application, in the negative electrode film, the protective component may be referred to as a second protective component.
[0088] As some improvements to the negative electrode film, in the X-ray diffraction spectrum of the protective component (second protective component), there are diffraction peaks at the positions of diffraction angles 2θ of 27°±0.5°, 30°±0.5°, 32.5°±0.5°, 40.5°±0.5°, and 50°±0.5°, respectively;
[0089] In the present application, the protective component (second protective component) has diffraction peaks at diffraction angles 2θ of 27°±0.5°, 30°±0.5°, 32.5°±0.5°, 40.5°±0.5°, and 50°±0.5° in an X-ray diffraction spectrum measured by an X-ray diffraction apparatus (XRD) using CuKα1.
[0090] X-ray diffraction analysis spectrum is well known in the art and can be tested by methods known in the art. For example, the X-ray diffraction analysis spectrum of compound A can be measured using CuKα1 radiation with reference to JIS K 0131-1996 General Rules for X-ray Diffraction Analysis.
[0091] As some improvements to the negative electrode film, the active material is a negative electrode active material, and the negative electrode active material can adopt the negative electrode active material for batteries known in the art. The present application has no particular restrictions on the type of negative electrode active material, as long as the purpose of the present application can be achieved. As an example, the negative electrode active material includes, but is not limited to, one or more of lithium titanate, metal Li, In, Sn and their respective alloys, carbon-based materials or silicon-based materials.
[0092] As an example, the negative electrode active material may be selected from lithium titanate.
[0093] Alternatively, the negative electrode active material may be selected from metals Li, In, Sn and their respective alloys.
[0094] Alternatively, the negative electrode active material may be selected from carbon-based materials, such as graphite, hard carbon, soft carbon, mesocarbon microbeads, and carbon-based active materials of highly oriented pyrolytic graphite.
[0095] Alternatively, the negative electrode active material may be selected from silicon-based materials, such as Si single substance, Si alloy, silicon oxide, Si-based active materials of silicon carbon, and the like.
[0096] However, the present application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0097] As some improvements to the negative electrode film, the particle size of the active material, that is, the negative electrode active material, is 20nm to 40μm; as an example, the particle size of the positive electrode active material can be any point value of 20nm, 30nm, 50nm, 80nm, 100nm, 500nm, 800nm, 1μm, 10μm, 20μm, 30μm, 40μm or any range value between two points. By making the particle size of the negative electrode active material in the above appropriate range, the processing performance of the material can be improved, and the capacity advantage can also be brought into play, so that the comprehensive electrical performance of the negative electrode film is better. If the particle size is too small, it will affect the energy density, and if the particle size is too large, it will reduce the capacity.
[0098] Furthermore, the following technical features can be applied to both positive electrode membranes and negative electrode membranes, that is, no matter whether the electrode membrane is a positive electrode membrane or a negative electrode membrane, the following technical features can be universally used.
[0099] As some improvements of electrode membranes such as positive electrode membranes or negative electrode membranes, sulfide solid electrolytes include but are not limited to Li x MP y S z (M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12), Li 7-x-y PS 6-x- y Cl x X y 、(X is a halogen element, 0≤x≤1.7, 0≤y≤1.7), xLi 2 S·(100-x)P 2 S 5 (70≤x≤80) or yLiI·zLiBr·(100-yz)(xLi 2 S·(100-x)P 2 S 5 )(70≤x≤80, 0≤y≤30, 0≤z≤30) or more.
[0100] As an example, the sulfide solid electrolyte may be selected from Li x MP y S z , wherein M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12.
[0101] Alternatively, the sulfide solid electrolyte can be selected from Li 7-x-y PS 6-x-y Cl x X y , wherein X is a halogen element, 0≤x≤1.7, 0≤y≤1.7.
[0102] Alternatively, the sulfide solid electrolyte may be selected from xLi 2 S·(100-x)P 2 S 5 , where 70≤x≤80.
[0103] Alternatively, the sulfide solid electrolyte can be selected from yLiI·zLiBr·(100-yz)(xLi 2 S·(100-x)P 2 S 5 ), where 70≤x≤80, 0≤y≤30, and 0≤z≤30.
[0104] The above-mentioned sulfide solid electrolytes may be used alone or in combination of two or more.
[0105] As some improvements of electrode films such as positive electrode films or negative electrode films, the particle size of the sulfide solid electrolyte is 10nm to 20μm. As an example, the particle size of the sulfide solid electrolyte can be any one of 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 500nm, 800nm, 1μm, 10μm, 20μm or a range between any two of them.
[0106] As some improvements of electrode membranes such as positive electrode membranes or negative electrode membranes, the mass ratio of the sulfide solid electrolyte to the mass ratio of the active material is 1:9 to 4:6. As an example, the mass ratio of the sulfide solid electrolyte to the mass ratio of the active material can be 1:9, 2:8, 3:7, 4:6, etc.
[0107] By controlling the mass ratio of the sulfide solid electrolyte and the active material within the above range, it is helpful to give full play to the role of the sulfide solid electrolyte and enhance the conduction of lithium ions, that is, to achieve rapid conduction of lithium ions in the positive electrode membrane or the negative electrode membrane, which is beneficial to improving the electrochemical performance of the battery.
[0108] As some improvements of electrode films such as positive electrode films or negative electrode films, in the electrode film, the mass content of the conductive agent is 0.05% to 5%, and the mass content of the binder is 0.05% to 5%. As an example, the mass proportion of the conductive agent in the electrode film can be 0.05%, 0.06%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5% or any range between the two. The mass proportion of the binder in the electrode film can be 0.05%, 0.06%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5% or any range between the two.
[0109] It should be pointed out that the present application has no particular restrictions on the types of conductive agents and binders in the electrode film, as long as the purpose of the present application can be achieved.
[0110] As an example, the binder in the electrode membrane can be selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), nitrile rubber (NBR), styrene-butadiene latex (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), polymethacrylic acid (PMAA), etc.
[0111] As an example, the conductive agent in the electrode film can be selected from at least one of conductive carbon black (such as acetylene black, Ketjen black, etc.), carbon nanotubes (CNTs), carbon nanofibers (CNFs), vapor grown carbon fibers (VGCFs), graphite, etc.
[0112] Optionally, the preparation process of the electrode film may further include a solvent, and the solvent includes but is not limited to at least one of butyl butyrate, toluene, xylene, diisobutyl ketone, and the like.
[0113] It should be pointed out that the electrode membrane of the present application can be prepared as a positive electrode membrane or a negative electrode membrane by a wet or dry film forming process, wherein no solvent is required during the dry film forming process.
[0114] As some improvements of electrode membranes such as positive electrode membranes or negative electrode membranes, the mass of the protective component is A, the sum of the mass of the active material and the sulfide solid electrolyte is B, and A and B satisfy: A is 0.1% to 10% of B. In the present application, the mass of the protective component can be 0.1% to 10% of the mass of the active material and the sulfide solid electrolyte. As an example, A is 0.1%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 6%, 8%, 10% of B, any one point value or any range value between two.
[0115] As some improvements of electrode films such as positive electrode films or negative electrode films, the thickness of the surface protection layer is ≤200nm. As an example, the thickness of the surface protection layer can be 200nm, 100nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm, 10nm or less than 10nm, etc.
[0116] In the present application, the thickness of the surface protective layer on the surface of the active material or sulfide solid electrolyte can be measured by a method known in the art, for example, by a transmission electron microscope (TEM).
[0117] Therefore, based on the above, it can be seen that in the process of modifying the surface of the active material and the electrolyte, the present invention selects compounds with ionic conductivity, and does not introduce other substances, which will not affect the lithium ion transmission at the interface of the active material. In addition, the added compound interacts with the surface of the active material and the electrolyte to form a surface protection layer on the surface, which can effectively improve the problems of element mutual diffusion and interface side reactions during the battery cycle. In addition, the modification process can be achieved by low-temperature sintering, which has the advantages of simple process flow and low energy consumption.
[0118] [Method for preparing electrode film]
[0119] Accordingly, in some embodiments, the present application provides a method for preparing an electrode film, the method comprising the following steps:
[0120] mixing an active material, a sulfide solid electrolyte, and a protective component precursor to obtain a mixture;
[0121] sintering the mixture to form a surface protection layer on the surface of the active material and / or the sulfide solid electrolyte to obtain a composite material;
[0122] The composite material is mixed with a conductive agent and a binder, and an electrode film is prepared through a film-forming process.
[0123] As mentioned above, the electrode film of the present invention can be a positive electrode film or a negative electrode film. When the electrode film is a positive electrode film, the protective component can be called a first protective component; when the electrode film is a negative electrode film, the protective component can be called a second protective component.
[0124] Thus, the preparation of the electrode film may include: mixing the raw materials for preparing the first protective component and the second protective component by mechanical ball milling to obtain the precursor of the first protective component and the precursor of the second protective component, the precursor of the first protective component is mixed with the sulfide solid electrolyte and the positive electrode active material, and the precursor of the second protective component is mixed with the sulfide solid electrolyte and the negative electrode active material. Through simple low-temperature sintering, the precursor of the first protective component is on the surface of the sulfide solid electrolyte and the positive electrode active material, and the precursor of the second protective component is on the surface of the sulfide solid electrolyte and the negative electrode active material to form a dense surface protective layer of the first protective component and the second protective component. Further, the formed composite material is mixed with a conductive agent and a binder, and the electrode film is obtained by a film forming process. Thus, while ensuring that the surface of the material has high ion conductivity, the effect of inhibiting the mutual diffusion of elements and surface side reactions between the active material and the sulfide solid electrolyte is achieved. On this basis, a high ion conductive sulfide solid electrolyte is used in the positive and negative electrode layers to achieve rapid conduction of lithium ions in the positive and negative electrode layers, and ultimately improve the electrochemical performance of the battery.
[0125] In the present invention, surface modification can be achieved only by mixing and sintering, the process flow is simple, and it is conducive to industrial application.
[0126] It should be understood that all the features and advantages described above for the “electrode membrane” are also applicable to the “method for preparing the electrode membrane” and will not be described in detail here.
[0127] In some specific embodiments, the method for preparing the electrode film specifically comprises the following steps (a) to (c):
[0128] (a) Preparing a mixture.
[0129] In step (a), preparing the mixture specifically includes: mixing the active material, the sulfide solid electrolyte and the protective component precursor to obtain a mixture.
[0130] When the electrode membrane is a positive electrode membrane, the first protective component synthesis raw material is mechanically mixed and then added to the positive electrode active material and the sulfide solid electrolyte for ball milling mixing, so that the precursor of the first protective component adheres to the surface of the positive electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0131] When the electrode membrane is a negative electrode membrane, the synthetic raw materials of the second protective component are mechanically mixed and then added to the negative electrode active material and the sulfide solid electrolyte for ball milling mixing, so that the precursor of the second protective component adheres to the surface of the negative electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0132] Optionally, in step (a), the electrode film is a positive electrode film, and the protective component precursor, that is, the precursor of the first protective component, includes a lithium source and a halogen compound. The raw materials for preparing the first protective component in the positive electrode film include a lithium source and a halogen compound, wherein the lithium source includes but is not limited to LiOH, Li 2 CO 3 or Li 2 O, halogen compounds including but not limited to NbCl 5 、TaCl 5 、ZrCl 4 、AlCl 3 、FeCl 3 , YCl 3 ,NbF 5 or TaF 5 Any one or a combination of at least two of the above. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0133] Optionally, in step (a), the electrode film is a negative electrode film, the protective component precursor, that is, the precursor of the second protective component includes a lithium source, a phosphorus source, and an oxide or sulfide, and the raw materials for preparing the second protective component in the negative electrode film include a lithium source, a phosphorus source, and an oxide or sulfide. Among them, the lithium source includes but is not limited to LiOH, Li 2 CO 3 , Li 2 O or Li 2 One or more of S, phosphorus sources include but are not limited to P 2 S 5 or P 2 O 5 One or more of the oxides or sulfides including but not limited to SnS 2 , Sb 2 S 3 , B 2 O 3 、Bi 2 O 3 SnO 2 、ZnO 2 , Fe 2 O 3 Any one or a combination of at least two of the above. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0134] Optionally, in step (a), the mixing is performed by ball milling, the ball milling is performed in an inert atmosphere (such as an inert atmosphere such as argon), the ball milling speed is 200 rpm to 800 rpm, and the ball milling time is 1 hour to 20 hours; preferably, the ball milling speed is 300 rpm to 600 rpm, and the ball milling time is 1 hour to 12 hours. By maintaining an inert atmosphere in the ball mill tank, the reaction between the sulfide solid electrolyte and the air can be avoided during the ball milling process.
[0135] (b) Preparation of composite materials.
[0136] In step (b), preparing the composite material specifically includes: sintering the mixture obtained in step (a) to form a surface protection layer on the surface of the active material and / or the sulfide solid electrolyte to obtain the composite material.
[0137] In step (b), by sintering the composite materials such as the positive and negative electrode composite materials at low temperature, surface protection layers can be formed on the surfaces of the positive and negative active materials and / or the surface of the sulfide solid electrolyte.
[0138] Optionally, in step (b), the sintering is low-temperature sintering, the temperature of the low-temperature sintering is 90° C. to 350° C., and the time of the low-temperature sintering is 1 h to 12 h.
[0139] Preferably, the temperature of the low-temperature sintering is 100° C. to 300° C., and the time of the low-temperature sintering is 2 h to 8 h.
[0140] (c) Preparation of electrode membrane.
[0141] In step (c), preparing the electrode film specifically includes: mixing the composite material obtained in step (b) with a conductive agent and a binder, and obtaining the electrode film through a film-forming process.
[0142] In the step (c), a conductive agent may be added to the sintered composite material powder for ball milling dispersion, and then a binder and a solvent (dispersant) may be added and mixed continuously, and then a film may be formed through a film forming process.
[0143] Optionally, the film forming process may be a wet film forming process or a dry film forming process.
[0144] It should be understood that the film forming process can be a dry or wet film forming process known in the prior art, and its specific operation method can refer to the prior art. This application does not limit its specific implementation process, and the operation can be selected according to actual conditions.
[0145] It should also be noted that no solvent is required during dry film formation.
[0146] Optionally, the electrode membrane preparation process is carried out in an environment with a dew point of less than -50°C.
[0147] In the present application, all preparation processes are carried out in an environment with a dew point of less than -50°C, which can prevent the reaction of moisture with the sulfide solid electrolyte.
[0148] Furthermore, when the electrode membrane of the present application is applied to a battery, an all-solid-state battery can be made by stacking the positive electrode membrane, the electrolyte layer and the negative electrode membrane in sequence.
[0149] Therefore, the modification process of the present invention can be achieved through low-temperature sintering, which has the advantages of simple process flow and low energy consumption.
[0150] In the present invention, the precursor of the first protective component and the precursor of the second protective component are respectively contacted with the positive and negative electrode active materials and the electrolyte and then sintered at low temperature to form a surface protective layer on the surface of the active material and the electrolyte, while ensuring that the material surface has high ion conductivity, the effect of inhibiting the mutual diffusion of elements and surface side reactions between the active material and the sulfide solid electrolyte is achieved. On this basis, the use of sulfide solid electrolytes in the positive and negative electrode layers can achieve rapid conduction of lithium ions in the positive and negative electrode layers, and ultimately improve the electrochemical performance of the battery.
[0151] [Battery]
[0152] like Figures 1 to 3As shown, in some embodiments, the present application provides a battery 12, which includes the electrode film as described above or the electrode film prepared according to the aforementioned method.
[0153] Optionally, the battery 12 is a solid-state battery. The solid-state battery 12 may be an all-solid-state battery or a semi-solid-state battery, preferably an all-solid-state battery.
[0154] In the present application, the battery 12 includes a positive electrode collector 5, a positive electrode film 4, a solid electrolyte layer 3, a negative electrode film 2 and a negative electrode collector 1 stacked in sequence; wherein the positive electrode film 5 includes the aforementioned electrode film or an electrolytic film prepared according to the aforementioned method; and / or, the negative electrode film 2 includes the aforementioned electrode film or an electrolytic film prepared according to the aforementioned method.
[0155] The battery of the present application may include a positive electrode sheet, a solid electrolyte layer 3 and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode current collector 5 and a positive electrode film 4, and the negative electrode sheet includes a negative electrode current collector 1 and a negative electrode film 2. At least one of the positive electrode sheet and the negative electrode sheet has an electrode film provided by any of the above embodiments of the present application.
[0156] As an example, in some cases, such as Figure 1 As shown, in the battery 12, the positive electrode sheet contains the electrode film (positive electrode film) provided in the present application. That is, the battery 12 includes a negative electrode current collector 1, a negative electrode film 2, a solid electrolyte layer 3, a positive electrode film 4 and a positive electrode current collector 5 stacked in sequence; wherein the positive electrode film 4 contains a sulfide solid electrolyte 6, a positive electrode active material 7 and a surface protective layer 8 formed by protective components, and includes from the inside to the outside: a core positive electrode active material 7, a surface protective layer 8, a sulfide solid electrolyte 6 and a surface protective layer 8.
[0157] Or, in other cases, such as Figure 2 As shown, in the battery 12, the negative electrode sheet contains the electrode film (negative electrode film) provided in the present application. That is, the battery 12 includes a negative electrode current collector 1, a negative electrode film 2, a solid electrolyte layer 3, a positive electrode film 4 and a positive electrode current collector 5 stacked in sequence; wherein the negative electrode film 2 contains a sulfide solid electrolyte 9, a negative electrode active material 10 and a surface protective layer 11 formed by protective components, and from the inside to the outside, it includes: a core negative electrode active material 10, a surface protective layer 11, a sulfide solid electrolyte 9 and a surface protective layer 11.
[0158] Or, in some cases, such as Figure 3As shown, in the battery 12, the positive electrode sheet contains the electrode film (positive electrode film) provided in the present application, and at the same time, the negative electrode sheet contains the electrode film (negative electrode film) provided in the present application. That is, the battery 12 includes a negative electrode current collector 1, a negative electrode film 2, a solid electrolyte layer 3, a positive electrode film 4 and a positive electrode current collector 5 stacked in sequence; wherein, the negative electrode film 2 contains a sulfide solid electrolyte 9, a negative electrode active material 10 and a surface protective layer 11 formed by a protective component, and from the inside to the outside, it includes: a core negative electrode active material 10, a surface protective layer 11, a sulfide solid electrolyte 9 and a surface protective layer 11. The positive electrode film 4 contains a sulfide solid electrolyte 6, a positive electrode active material 7 and a surface protective layer 8 formed by a protective component, and from the inside to the outside, it includes: a core positive electrode active material 7, a surface protective layer 8, a sulfide solid electrolyte 6 and a surface protective layer 8.
[0159] It should be pointed out that the present application has no particular restrictions on the materials of the positive electrode current collector and the negative electrode current collector, as long as the purpose of the present application can be achieved, and they can be selected according to actual needs.
[0160] In some embodiments, in the battery, the solid electrolyte in the solid electrolyte layer may be a halide electrolyte, a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte, or any other solid electrolyte material known in the art.
[0161] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0162] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.
[0163] Example 1
[0164] The preparation of the battery includes the following steps:
[0165] (1) Preparation of positive electrode film: 0.86 g NbCl 5 , 0.19 g ZrCl 4 and 0.096 g LiOH, and milled at 650 rpm for 10 h. Then 7 g positive electrode active material (LiCoO 2 ) and 3g sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 1.0 Br 0.6) are ball-milled and mixed at a rotation speed of 400 rpm for 2 hours to allow the protective component precursor to adhere to the surface of the positive electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0166] The mixture is sintered at 100° C. for 3 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the positive electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0167] The chemical formula of the protective component formed is LiNb 0.8 Zr 0.2 OCl 3.8 .
[0168] Conductive agent VGCF was added to the above composite material, and ball milling was performed at 300 rpm in an argon atmosphere for 5 hours. Then, binder PTFE was added for further mixing. The mass of VGCF and PTFE was 2% and 0.05% of the total mass respectively. Then, the positive electrode membrane was obtained through a roller pressing film forming process.
[0169] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 5.4 PS 4.4 Cl 1.0 Br 0.6 After being mixed with the binder PTFE in a ratio of 99:1, it is rolled and pressed into a solid electrolyte membrane, that is, a solid electrolyte layer.
[0170] (3) Preparation of negative electrode film: negative electrode active material graphite, sulfide solid electrolyte Li 6 PS 5 Cl, conductive agent CNF and binder PTFE were mixed in a ratio of 60:40:3:1 and then rolled to form a negative electrode membrane.
[0171] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in the order of battery cells, package them into sulfide all-solid-state batteries, and conduct battery charge and discharge performance tests. All of the above preparation processes are carried out in an environment with a dew point of less than -50°C to prevent moisture from reacting with the sulfide solid electrolyte.
[0172] Example 2
[0173] The preparation of the battery includes the following steps:
[0174] (1) Preparation of negative electrode film: 0.24 g Li 2 O, 0.60g P 2 S 5 and 0.16 g SnO 2Mix, ball mill at 650 rpm for 10 h, add 7 g of negative electrode active material (silicon carbon) and 3 g of sulfide solid electrolyte (Li 6 PS 5 Cl), and ball milled at a rotation speed of 300 rpm for 3 h to allow the protective component precursor to adhere to the surface of the negative electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0175] The mixture is sintered at 300° C. for 1.5 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the negative electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0176] The chemical formula of the protective component formed is Li 7.5 P 2.5 Sn 0.5 S 6.25 O 4.75 .
[0177] Conductive agent CNF was added to the above composite material, and the mixture was ball-milled at 400 rpm in an argon atmosphere for 3 hours. Binder SBR and solvent butyl butyrate were then added for further mixing, with the mass of CNF and SBR accounting for 2% and 3% of the total mass. The negative electrode membrane was then obtained through a wet film-forming process.
[0178] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The electrolyte membrane is made by mixing the binder SBR and the solvent butyl butyrate through a wet film forming process. 5.5 PS 4.5 Cl 1.5 The mass ratio of SBR is 98:2, that is, a solid electrolyte layer is obtained.
[0179] (3) Preparation of positive electrode film: LiNi 0.8 Co 0.1 Mn 0.1 O 2 , sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The electrolyte membrane is made by mixing the conductive agent CNF, the binder SBR and the solvent butyl butyrate through a wet film forming process. 0.8 Co 0.1 Mn 0.1 O 2 :Li 5.5 PS 4.5 Cl 1.5 : The mass ratio of CNF:SBR is 70:30:5:2.
[0180] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in the order of battery cells, package them into sulfide all-solid-state batteries, and conduct battery charge and discharge performance tests. All of the above preparation processes are carried out in an environment with a dew point of less than -50°C to prevent moisture from reacting with the sulfide solid electrolyte.
[0181] Example 3
[0182] The preparation of the battery includes the following steps:
[0183] (1) Preparation of positive electrode film: 0.38 g NbCl 5 , 0.14g ZrCl 4 and 0.049 g LiOH, ball milled at 650 rpm for 10 h, and 8 g Li 2 ZrO 3 LiNi after coating 0.6 Co 0.2 Mn 0.2 O 2 Positive electrode active material and 2g sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.0 Br 0.5 ) are ball-milled and mixed at a rotation speed of 200 rpm for 5 hours to allow the protective component precursor to adhere to the surface of the positive electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0184] The mixture is sintered at 120° C. for 2 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the positive electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0185] The chemical formula of the protective component formed is LiNb 0.7 Zr 0.3 OCl 3.7 .
[0186] Conductive agent VGCF was added to the above composite material, and the mixture was ball-milled at 600 rpm in an argon atmosphere for 2 hours. Binder NBR and solvent xylene were then added for further mixing, with the mass of VGCF and NBR accounting for 2% and 2% of the total mass respectively. The positive electrode film was then obtained through a wet film-forming process.
[0187] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 6 PS 5Cl, binder NBR and solvent xylene are mixed to form an electrolyte membrane through a wet film forming process, wherein Li 6 PS 5 The mass ratio of Cl to NBR is 98:2, that is, a solid electrolyte layer is obtained.
[0188] (3) Preparation of negative electrode film: 0.13 g Li 2 O, 0.35g P 2 S 5 、0.019gSb 2 O 3 , 8g negative electrode active material (silicon carbon) and 2g sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.0 Br 0.5 ), and ball milled at a rotation speed of 300 rpm for 3 h to allow the protective component precursor to adhere to the surface of the negative electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0189] The mixture is sintered at 280° C. for 1.5 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the negative electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0190] The chemical formula of the protective component formed is Li 7.4 P 2.8 Sb 0.2 S 7 O 4 .
[0191] Conductive agent CNF was added to the above composite material, and the mixture was ball-milled at 400 rpm in an argon atmosphere for 3 hours. Then, binder SBR and solvent xylene were added for further mixing, with the mass of CNF and SBR accounting for 2% and 2% of the total mass respectively. The negative electrode membrane was then obtained through a wet film forming process.
[0192] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in the order of battery cells, package them into sulfide all-solid-state batteries, and conduct battery charge and discharge performance tests. All of the above preparation processes are carried out in an environment with a dew point of less than -50°C to prevent moisture from reacting with the sulfide solid electrolyte.
[0193] Example 4
[0194] The preparation of the battery includes the following steps:
[0195] (1) Preparation of positive electrode film: Under argon atmosphere, 0.29 g TaCl 5 , 0.018g YCl3 and 0.022 g LiOH, ball milled at 650 rpm for 10 h, and 7 g positive electrode active material (LiFePO 4 ) and 3g sulfide solid electrolyte (15LiBr·10LiI·75(0.75Li 2 S·0.25P 2 S 5 )) ball milling and mixing at a rotation speed of 400 rpm for 3 hours to allow the protective component precursor to adhere to the surface of the positive electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0196] The mixture is sintered at 300° C. for 2 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the positive electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0197] The chemical formula of the protective component formed is LiTa 0.9 Y 0.1 OCl 3.8 .
[0198] Conductive agent CNF was added to the above composite material, and the mixture was ball-milled at 500 rpm for 2 hours in an argon atmosphere. Then, binder SBR and solvent butyl butyrate were added for further mixing, with the mass of CNF and SBR being 5% and 2% of the total mass respectively. The positive electrode membrane was then obtained through a wet film forming process.
[0199] (2) Preparation of solid electrolyte layer: 0.75Li sulfide solid electrolyte 2 S·0.25P 2 S 5 The electrolyte membrane is made by mixing the binder SBR and the solvent butyl butyrate through a wet film forming process. Among them, 0.75Li 2 S·0.25P 2 S 5 The mass ratio of SBR is 99:1, that is, a solid electrolyte layer is obtained.
[0200] (3) Preparation of negative electrode film: negative electrode active material micron Si, sulfide solid electrolyte 0.75Li 2 S·0.25P 2 S 5 , conductive agent CNF, binder SBR and solvent butyl butyrate were mixed and made into negative electrode film by wet film forming process, among which micron Si, 0.75Li 2 S·0.25P 2 S 5 The mass ratio of CNF and SBR is 60:40:5:2.
[0201] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in the order of battery cells, package them into sulfide all-solid-state batteries, and conduct battery charge and discharge performance tests. All of the above preparation processes are carried out in an environment with a dew point of less than -50°C to prevent moisture from reacting with the sulfide solid electrolyte.
[0202] Example 5
[0203] The preparation of the battery includes the following steps:
[0204] (1) Preparation of positive electrode film: 0.79 g TaCl 5 , 0.040 g FeCl 3 Mix with 0.059 g LiOH, ball mill at 650 rpm for 10 h, add 7 g LiNbO 3 LiNi after coating 0.8 Co 0.1 Mn 0.1 O 2 The positive electrode active material and 2.5g sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.0 F 0.5 ) are ball-milled and mixed at a rotation speed of 300 rpm for 3 hours to allow the protective component precursor to adhere to the surface of the positive electrode active material and the sulfide solid electrolyte to obtain a mixture.
[0205] The mixture is sintered at 300° C. for 1.5 hours, and the protective component precursor forms a surface protective layer formed by the protective component on the surface of the positive electrode active material and the sulfide solid electrolyte. The sintering atmosphere is argon gas, and a composite material is obtained.
[0206] The chemical formula of the protective component formed is LiTa 0.9 Fe 0.1 OCl 3.8 .
[0207] Conductive agent CNF was added to the above composite material, and the mixture was ball-milled at 400 rpm in an argon atmosphere for 3 hours. Then, binder SBR and solvent butyl butyrate were added for further mixing, with the mass of CNF and SBR being 5% and 2% of the total mass respectively. The positive electrode membrane was then obtained through a wet film forming process.
[0208] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 6 PS 5 Cl, binder SBR and solvent butyl butyrate were mixed and then the electrolyte membrane was prepared by wet film forming process, wherein Li 6 PS 5The mass ratio of Cl to SBR is 98:2, that is, a solid electrolyte layer is obtained.
[0209] (3) Preparation of negative electrode film: Lithium metal thin film is used as the negative electrode film.
[0210] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in the order of battery cells, package them into sulfide all-solid-state batteries, and conduct battery charge and discharge performance tests. All of the above preparation processes are carried out in an environment with a dew point of less than -50°C to prevent moisture from reacting with the sulfide solid electrolyte.
[0211] Comparative Example 1
[0212] The preparation of the battery includes the following steps:
[0213] (1) Preparation of positive electrode film: LiCoO 2 , sulfide solid electrolyte Li 5.4 PS 4.4 Cl 1.0 Br 0.6 , the conductive agent VGCF and the binder PTFE were mixed in a mass ratio of 70:30:2:0.05 and then roll-pressed into a positive electrode membrane to obtain a positive electrode membrane.
[0214] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 5.4 PS 4.4 Cl 1.0 Br 0.6 After being mixed with the binder PTFE in a ratio of 99:1, it is rolled and pressed into a solid electrolyte membrane, that is, a solid electrolyte layer.
[0215] (3) Preparation of negative electrode film: negative electrode active material graphite, sulfide solid electrolyte Li 6 PS 5 Cl, conductive agent CNF and binder PTFE were mixed in a ratio of 60:40:3:1 and then rolled to form a negative electrode membrane.
[0216] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in this order to form a battery cell, package it into a sulfide all-solid-state battery, and conduct a battery charge and discharge performance test.
[0217] Comparative Example 2
[0218] The preparation of the battery includes the following steps:
[0219] (1) Preparation of negative electrode film: The negative electrode active material silicon carbon and sulfide solid electrolyte Li 6 PS 5 Cl 1.0, conductive agent CNF, binder SBR and solvent butyl butyrate are mixed and then the negative electrode film is made by wet film forming process. Among them, silicon carbon, Li 6 PS 5 Cl 1.0 The mass ratio of CNF and SBR is 70:30:2:3.
[0220] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The electrolyte membrane is made by mixing the binder SBR and the solvent butyl butyrate through a wet film forming process. 5.5 PS 4.5 Cl 1.5 The mass ratio of SBR is 98:2, that is, a solid electrolyte layer is obtained.
[0221] (3) Preparation of positive electrode film: LiNi 0.8 Co 0.1 Mn 0.1 O 2 , sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 , conductive agent CNF, binder SBR and solvent butyl butyrate are mixed and then the positive electrode film is made by wet film forming process. 0.8 Co 0.1 Mn 0.1 O 2 :Li 5.5 PS 4.5 Cl 1.5 The mass ratio of CNF:SBR was 70:30:5:2 to obtain a positive electrode film.
[0222] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in this order to form a battery cell, package it into a sulfide all-solid-state battery, and conduct a battery charge and discharge performance test.
[0223] Comparative Example 3
[0224] The preparation of the battery includes the following steps:
[0225] (1) Preparation of positive electrode film: Li 2 ZrO 3 LiNi after coating 0.6 Co 0.2 Mn 0.2 O 2 Positive electrode active material, sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.0Br 0.5 , conductive agent VGCF, binder NBR and solvent xylene are mixed and then the positive electrode film is made by wet film forming process. 0.6 Co 0.2 Mn 0.2 O 2 :Li 5.5 PS 4.5 Cl 1.0 Br 0.5 The mass ratio of VGCF:NBR is 80:20:2:2 to obtain a positive electrode film.
[0226] (2) Preparation of solid electrolyte layer: Sulfide solid electrolyte Li 6 PS 5 Cl, binder NBR and solvent xylene are mixed to form an electrolyte membrane through a wet film forming process, wherein Li 6 PS 5 The mass ratio of Cl to NBR is 98:2, that is, a solid electrolyte layer is obtained.
[0227] (3) Preparation of negative electrode film: The negative electrode active material silicon carbon and sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.0 Br 0.5 , conductive agent CNF, binder SBR and solvent xylene are mixed and then the negative electrode film is made by wet film forming process. Among them, silicon carbon, Li 5.5 PS 4.5 Cl 1.0 Br 0.5 The mass ratio of CNF and SBR is 80:20:2:2 to obtain a negative electrode membrane.
[0228] (4) Assemble the negative electrode current collector (copper foil), negative electrode membrane, electrolyte membrane, positive electrode membrane, and positive electrode current collector (aluminum foil) in this order to form a battery cell, package it into a sulfide all-solid-state battery, and conduct a battery charge and discharge performance test.
[0229] Performance Testing
[0230] The batteries obtained in the above embodiments and comparative examples were subjected to performance tests, specifically including:
[0231] 1) First charge and discharge test: The solid-state battery is charged and discharged at 0.1C constant current for one cycle at 25°C. The charge and discharge cut-off voltage and voltage range are 3.0-4.3V, and the first discharge specific capacity is recorded.
[0232] 2) First efficiency (first coulomb efficiency) test: First coulomb efficiency = first charge capacity / first discharge capacity*100%.
[0233] 3) Long cycle test: The solid-state battery is charged and discharged for 100 cycles at 0.1C constant current at 25°C, with a charge and discharge cut-off voltage and voltage range of 3.0-4.3V; the capacity after 100 cycles is recorded, and the capacity retention rate after 100 cycles is calculated. Among them, 100-cycle capacity retention rate = capacity after 100 cycles / first discharge specific capacity * 100%. This parameter can feedback the battery's cycle performance. The higher the value of the capacity retention rate, the better the battery cycle performance of this embodiment.
[0234] The test results are shown in Table 1 below.
[0235] Table 1 Electrochemical performance test results of batteries prepared in various embodiments and comparative examples
[0236]
[0237] As can be seen from Table 1, compared with Comparative Examples 1-3, the solid-state battery prepared using the electrode film of Examples 1-5 of the present invention has better first discharge specific capacity, first coulomb efficiency and capacity retention rate during the charge and discharge process, and improves the cycle performance and capacity of the battery. This shows that the compound added to the electrode film of the present invention, that is, the protective component, interacts with the surface of the active substance and the electrolyte to form a surface protective layer on the surface, has good compatibility with both the active substance and the electrolyte, can avoid the problem of interface side reactions of the battery in the electrochemical process, thereby effectively improving the comprehensive electrochemical performance of the battery.
[0238] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0239] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0240] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0241] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0242] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrode film, characterized in that: The electrode film comprises: an active material, a sulfide solid electrolyte, a conductive agent, a binder and a protective component; Wherein, at least part of the protective component is located on the surface of the active material to form a surface protective layer, and / or, at least part of the protective component is located on the surface of the sulfide solid electrolyte to form a surface protective layer; The protective component includes a composite oxide containing an alkali metal.
2. The electrode film according to claim 1, characterized in that The active material, the sulfide solid electrolyte and at least one layer of the surface protective layer form a core-shell structure, the core of the core-shell structure is the active material, the shell of the core-shell structure includes the sulfide solid electrolyte and at least one layer of the surface protective layer, and in a direction away from the core, the surface protective layer, the sulfide solid electrolyte, and the surface protective layer are arranged in sequence; The surface protective layer is formed of the protective component.
3. The electrode film according to claim 1, characterized in that The mass of the protective component is A, the sum of the masses of the active material and the sulfide solid electrolyte is B, and A and B satisfy: A is 0.1% to 10% of B. And / or, the thickness of the surface protection layer is ≤200 nm.
4. The electrode film according to any one of claims 1 to 3, characterized in that: The electrode film is a positive electrode film, and the chemical formula of the protective component is LiM a OX b , wherein M includes one or more of Ta, Nb, Zr, Al, Fe or Y, X includes one or more of Cl, Br or F, 0≤a≤1, 2≤b≤4.
5. The electrode film according to claim 4, characterized in that The positive electrode film satisfies at least one of the following characteristics (1) to (7): (1) In the X-ray diffraction spectrum of the protective component, there are diffraction peaks at the positions where the diffraction angle 2θ values are 14°±0.5°, 24.5°±0.5°, and 31°±0.5°, respectively; (2) The active material is a positive electrode active material, and the positive electrode active material includes LiCoO2, LiMnO2, LiNiO2, LiVO3, LiNi x Co y Mn z O2(x+y+z=1,0≤x<1,0≤y<1,0≤z<1), LiNi x Co y Al z O2 (x+y+z=1, 0≤x<1, 0≤y<1, 0≤z<1), xLi2MnO3·(1-x)LiTMO2 (TM=at least one of Ni, Mn, Co or Al, 0<x<1), LiMn2O4, Li4Ti5O 12 、Li(Ni 0.5 Mn 1.5 )O4, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 or LiMn x Fe 1- x One or more of PO4 (0<x<1); (3) The sulfide solid electrolyte includes Li x MP y S z (M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12), Li 7-x-y PS 6-x-y Cl x X y (X is a halogen element, 0≤x≤1.7, 0≤y≤1.7), xLi2S·(100-x)P2S5(70≤x≤80) or yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5)(70≤x≤80, 0≤y≤30, 0≤z≤30) or one or more thereof; (4) The particle size of the active substance is 20 nm to 50 μm; (5) The particle size of the sulfide solid electrolyte is 10 nm to 20 μm; (6) The mass ratio of the sulfide solid electrolyte to the active material is 1:9 to 4:6; (7) In the electrode film, the mass content of the conductive agent is 0.05% to 5%, and the mass content of the binder is 0.05% to 5%.
6. The electrode film according to any one of claims 1 to 3, characterized in that: The electrode film is a negative electrode film, and the chemical formula of the protective component is Li v P w N x S y O z , wherein N includes one or more of Sn, Sb, B, Bi, Fe or Zn, 7≤v≤10, 2≤w≤4, 0≤x≤1, 5≤y≤8, 0≤z≤5.
7. The electrode film according to claim 6, characterized in that The negative electrode film satisfies at least one of the following characteristics (1) to (7): (1) The protective component has an X-ray diffraction spectrum with diffraction peaks at diffraction angles 2θ of 27°±0.5°, 30°±0.5°, 32.5°±0.5°, 40.5°±0.5°, and 50°±0.5°, respectively; (2) The active material is a negative electrode active material, and the negative electrode active material includes one or more of lithium titanate, metal Li, In, Sn and their respective alloys, carbon-based materials or silicon-based materials; (3) The sulfide solid electrolyte includes Li x MP y S z (M includes one or more of Sn, Ge or Si, 0<x≤10, 0<y≤2, 0<z≤12), Li 7-x-y PS 6-x-y Cl x X y (X is a halogen element, 0≤x≤1.7, 0≤y≤1.7), xLi2S·(100-x)P2S5(70≤x≤80) or yLiI·zLiBr·(100-yz)(xLi2S·(100-x)P2S5)(70≤x≤80, 0≤y≤30, 0≤z≤30) or one or more thereof; (4) The particle size of the active substance is 20 nm to 40 μm; (5) The particle size of the sulfide solid electrolyte is 10 nm to 20 μm; (6) The mass ratio of the sulfide solid electrolyte to the active material is 1:9 to 4:6; (7) In the electrode film, the mass content of the conductive agent is 0.05% to 5%, and the mass content of the binder is 0.05% to 5%.
8. The method for preparing an electrode film according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing an active material, a sulfide solid electrolyte, and a protective component precursor to obtain a mixture; sintering the mixture to form a surface protection layer on the surface of the active material and / or the sulfide solid electrolyte to obtain a composite material; The composite material is mixed with a conductive agent and a binder, and the electrode film is prepared through a film-forming process.
9. The method for preparing an electrode film according to claim 8, characterized in that: The preparation method satisfies at least one of the following characteristics (1) to (6): (1) The electrode film is a positive electrode film, and the protective component precursor includes a lithium source and a halogen compound, wherein the lithium source includes one or more of LiOH, Li2CO3 or Li2O, and the halogen compound includes one or more of NbCl5, TaCl5, ZrCl4, AlCl3, FeCl3, YCl3, NbF5 or TaF5; (2) The electrode film is a negative electrode film, and the protective component precursor includes a lithium source, a phosphorus source, and an oxide or sulfide, wherein the lithium source includes one or more of LiOH, Li2CO3, Li2O, or Li2S, the phosphorus source includes one or more of P2S5 or P2O5, and the oxide or sulfide includes one or more of SnS2, Sb2S3, B2O3, Bi2O3, SnO2, ZnO2, and Fe2O3; (3) In the step of obtaining the mixture, the mixing is performed by ball milling, the ball milling is performed in an inert atmosphere, the rotation speed of the ball mill is 200 rpm to 800 rpm, and the ball milling time is 1 h to 20 h; (4) In the step of obtaining the composite material, the sintering is low-temperature sintering, the temperature of the low-temperature sintering is 90° C. to 350° C., and the time of the low-temperature sintering is 1 h to 12 h; (5) The film forming process includes a wet film forming process or a dry film forming process; (6) The electrode membrane preparation process is carried out in an environment with a dew point of less than -50°C.
10. A battery, characterized in that: The battery comprises a positive electrode current collector, a positive electrode film, a solid electrolyte layer, a negative electrode film and a negative electrode current collector which are stacked in sequence; Wherein, the positive electrode film comprises the electrode film according to any one of claims 1 to 7 or the electrolytic film prepared by the method according to any one of claims 8 to 9; And / or, the negative electrode film comprises the electrode film according to any one of claims 1 to 7 or the electrolytic film prepared according to the method according to any one of claims 8 to 9.
Citation Information
Cited By
Positive plate and preparation method thereof, all-solid-state battery, battery assembly and electric equipment
CN120261477A
Sulfide solid electrolyte for inhibiting dendritic crystal growth, preparation method and application
CN121839852A